Anatomical Variations and Clinical Significance of the Frozen Shoulder Variant: A Cross-Sectional Study in the Pakistani Population - Asma Zulfiqar, Sitwat Amna, Muhammad Faisal Khan, Piriha Abbasi, Saba Saleem Safdar, Uzma Ali, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The shoulder joint, known for its complexity and mobility, exhibits anatomical variations that may affect clinical outcomes. A newly observed configuration—provisionally termed the "Frozen Shoulder" variant—includes atypical glenohumeral articulation, altered muscular insertions, and subtle bony outgrowths. Despite anecdotal reports, this variant remains underreported in global literature. Aims and Objectives: This study aims to investigate its prevalence and clinical significance in the Pakistani population. Methods: A descriptive cross-sectional study was conducted from January to December 2022 at Jinnah Hospital, Lahore. A total of 200 adult patients (aged 18–70) undergoing shoulder imaging for non-traumatic causes were enrolled. Radiological evaluations included MRI and X-rays, assessed independently by two musculoskeletal radiologists. Clinical assessments included Constant-Murley and Visual Analog Scale (VAS) scores. Additionally, 10 cadaveric shoulders were dissected for anatomical validation. Statistical analyses were performed using SPSS v26, with significance set at p < 0.05. Results: The Frozen Shoulder variant was present in 28% (n = 56) of patients. The highest prevalence (37.5%) was observed in the 31–45 age group, though differences across age and gender were not statistically significant (p > 0.05). Patients with the variant reported slightly higher VAS pain scores (3.67 ± 1.18) compared to controls (3.43 ± 1.21), but functional capacity remained similar (Constant-Murley score ~71.5). Cadaveric dissection confirmed consistent anatomical deviations. Conclusion: The Frozen Shoulder variant is a common and clinically relevant anatomical variation in the Pakistani population. Its recognition is crucial for accurate diagnosis, surgical planning, and development of population-specific clinical protocols. Keywords: Frozen Shoulder, Anatomical Variation, Glenohumeral Joint, Clinical Anatomy, Pakistani Population